Existence and Uniqueness of Equilibrium In First Place Auctions and War of Attrition with Affiliated Values - Alessandro Lizzeri; Nicola Persico (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1995)
We prove existence and uniqueness of equilibrium in a 2-bidder asymmetric first price auction with affiliated values. The techniques used to prove uniqueness are different from the ones used in analyses of private values environments. Moreover the proof of existence is constructive. For comparison purposes we also consider the war of attrition and show that there is a continuum of equilibria in that game.
Keywords: 330